Edward Stanly : Whiggery's tarheel "conqueror" - Brown, Norman D. (University : University of Alabama Press, 1974)
Raised under the "Ancient Standard of Federalism," Edward Stanly was a southern nationalist during a time of popular nullification and secession doctrines. Edward Stanly: Whiggery's Tarheel Conqueror is an unprecedented biography of Stanly's life, and recounts his fiery and controversial emergence in the Whig Party of North Carolina in the 1930s, his role as a champion of Whiggery in the United States House of Representatives 1837-1843 and 1849-1853, his candidacy for governor of California in 1857, his appointment by President Abraham Lincoln as a military governor of N
Preface; 1. The Ancient Standard of Federalism; 2. Encounter With a Connecticut Nightingale; 3. The Little Conqueror; 4. On, Stanly, On!; 5. The War With Captain Tyler; 6. Apple of Discord; 7. A Most Extraordinary Course; 8. Stanly and the Party Divided; 9. In the Land of Gold; 10. Mission of Love; 11. A Barren Sceptre; 12. An Inveterate Old-Line Whig; Notes; Bibliography; Index.
Includes bibliographical references (pages 333-350) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Stanly, Edward, -- 1810-1872.; Stanly, Edward, -- 1810-1872; Legislators -- United States -- 19th century; Parlementaires -- États-Unis -- 19e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; United States -- Politics -- Stanly, Edward -- Biographies; Biographies; Biographies; Biographies